Flexural Behavior of Normal and Lightweight Concrete Composite Beams - Syahrul Syahrul; M. W. Tjaronge; Rudy Djamaluddin; A. A. Amiruddin (Civil Engineering Journal, 2021)
This paper presents an experimental study of the behavior of Normal Concrete Beams (NCB) and composite beams with lightweight foamed concrete (CB), reinforced with steel bar measuring 2 f 8 mm in the compressive section and 2 D 16 mm in the tensile section, shear steel bar f 8 mm. The sample consisted of two normal concrete beams (NCB) and two composite beams with lightweight foamed concrete (CB). The main variables in this study are the type of concrete, the type of steel bar and the flexural behavior. The beam samples were tested by two-point loading, failure mode and crack width were observed. The results showed that the flexural process of normal concrete blocks (NCB) and composite beams with lightweight foamed concrete (CB) was almost the same. There is no slip failure at the combined interface, the flexural capacity of the composite beam with lightweight foamed concrete can be calculated based on the statics analysis and plane-section assumptions. To calculate the ultimate capacity of a composite beam with lightweight foamed concrete is to convert a section consisting of more than one fc' to an equivalent section consisting of one fc'. Furthermore, it is validated by calculating the theoretical moment capacity and comparing the theoretical moment capacity of the experimental results. The results of the flexural test, composite beam with lightweight foamed concrete (CB) showed ductile deflection behavior, diagonal crack patterns, and low flexural capacity of the beam (NCB). Doi: 10.28991/cej-2021-03091673 Full Text: PDF